Strategi Bisnis Digital Mahasiswa Universitas Muhammadiyah Palopo Dalam Meningkatkan Penjualan Produk - Nurlela; Ardianti Amir; Tia Juliawati; Vilsya Delia; Suraidah (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to determine the digital business strategy and product development on increasing student sales at the Muhammadiyah University of Palopo. This study was conducted using a quantitative method. The population and sample used were all 28 students. This research technique uses purpasive sampling technique, namely all students of the Muhammadiyah University of Palopo. The data used in this study is data in the form of questionnaires. From this study, it was found that there was an influence between the variables of digital business strategy (X1) product development (X2) on increasing sales (Y). This is proven through hypothesis testing using the t test. Where the results were obtained with a t count that was greater than the t table, namely t count (2.538)> t table (2.048). Reliability testing was carried out to measure the consistency of the research instrument using Cronbach's Alpha, and validity testing was carried out to ensure that the research instrument actually measured what should be measured. So that it is accepted or "Digital business strategy and product development have a significant effect on increasing sales at Muhammadiyah University of Palopo Students".